Metric magnetic resonance imaging analysis reveals pronounced substantia-innominata atrophy in dementia with Lewy bodies with a psychiatric onset - Hansen, Niels; Müller, Sebastian Johannes; Khadhraoui, Eya; Riedel, Christian Heiner; Langer, Philip; Wiltfang, Jens; Timäus, Charles-Arnold; Bouter, Caroline; Ernst, Marielle; Lange, Claudia (Frontiers in Aging Neuroscience, 2022)
Background: Dementia with Lewy bodies (DLB) is a type of dementia often diagnosed in older patients. Since its initial symptoms range from delirium to psychiatric and cognitive symptoms, the diagnosis is often delayed. Objectives: In our study, we evaluated the magnetic resonance imaging (MRI) of patients suffering from DLB in correlation with their initial symptoms taking a new pragmatic approach entailing manual measurements in addition to an automated volumetric analysis of MRI. Methods: 63 patients with diagnosed DLB and valid 3D data sets were retrospectively and blinded evaluated. We assessed atrophy patterns 1) manually for the substantia innominata and 2) via FastSurfer for the most common supratentorial regions. Initial symptoms were categorized by (1) mild cognitive impairment (MCI), (2) psychiatric episodes, and (3) delirium. Results: Manual metric MRI measurements revealed moderate, but significant substantia-innominata (SI) atrophy in patients with a psychiatric onset. Automatic volumetric MRI analysis failed to confirm those results. Conclusions: The SI in patients with DLB and a psychiatric-onset is more atrophied than that in patients with initial mild cognitive impairment. Our work shows that the latest basic volumetric segmentation algorithm does not detect every kind of atrophy.